2016
DOI: 10.1177/2050640615581966
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous combined balloon‐occluded retrograde transvenous obliteration and partial splenic embolization for gastric fundal varices

Abstract: Background: We previously reported the techniques and usefulness of simultaneous combined balloon-occluded retrograde transvenous obliteration (B-RTO) and partial splenic embolization (PSE), based on the hypothesis that concomitant PSE can diminish the increase in portal venous pressure after B-RTO. Objective: After experiencing more cases and performing longer-term follow-up, we re-evaluated the efficacy of simultaneous combined B-RTO and PSE for gastric fundal varices (GVs). Methods: We performed B-RTO in 36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…We use BRTO for both emergency and elective treatment of ruptured GVs as well as prophylactic treatment according to the criteria described below[ 15 , 16 ]. Indications for prophylactic treatment of GVs include nodular form and red color spot lesions[ 17 ], increasing size over time, and hepatic encephalopathy.…”
Section: Indications and Contraindications For Brtomentioning
confidence: 99%
See 3 more Smart Citations
“…We use BRTO for both emergency and elective treatment of ruptured GVs as well as prophylactic treatment according to the criteria described below[ 15 , 16 ]. Indications for prophylactic treatment of GVs include nodular form and red color spot lesions[ 17 ], increasing size over time, and hepatic encephalopathy.…”
Section: Indications and Contraindications For Brtomentioning
confidence: 99%
“…Indications for prophylactic treatment of GVs include nodular form and red color spot lesions[ 17 ], increasing size over time, and hepatic encephalopathy. However, we do not treat patients with severe hepatic dysfunction (total bilirubin ≥ 4.0 mg/dL, Child-Pugh score ≥ 13), renal dysfunction (eGFR < 30 mL/min/1.73 m 2 ), or other serious diseases with poor prognosis as well as those without a portosystemic shunt amenable to a retrograde approach[ 15 ]. We consider the presence of contrast agent flowing freely from the GRS into the portal vein on balloon-occluded retrograde venography (BRTV) a relative contraindication[ 16 ].…”
Section: Indications and Contraindications For Brtomentioning
confidence: 99%
See 2 more Smart Citations
“…A retrospective study of BRTO showed that the clinical success rate of BRTO-that is, no recurrence of GVs with no rebleeding-was 97.3%, confirming the efficacy of BRTO [7]. The combination of BRTO with PSE can decrease the portal venous pressure and prevent the exacerbation of EVs [8][9][10][11][12], and can significantly reduce the amount of the sclerosing agent required, including 5% EOI for BRTO [8]. However, exacerbation of EVs has been observed in 33.3% of patients treated with BRTO without PSE [7].…”
Section: Discussionmentioning
confidence: 87%